THE COPING STRATEGIES AND ITS RELATION WITH THE LEVEL OF PSYCHOLOGICAL WELL-BEING.A RESEARCH WITH ADOLESCENTS OF LOW SOCIOECONOMIC LEVEL OF TUCUMAN (ARGENTINA) - Figueroa, María Inés; Contini, Norma; Lacunza, Ana Betina; Levín, Mariel; Suedan, Alejandro Estévez (Anales de Psicología / Annals of Psychology, 2005)
Adolescence is a period in which happen physical and psychological changes. Coping strategies of adolescents in a low socioeconomic context were researched, related to psychological well-being level. How young people confront in an efficient and adaptive way the demands introduce to them was analyzed from a health model. The importance given to this subject is based on fact that coping strategies can be considered as possible factors of health protection. Objectives: 1) to identify and analyze coping strategies used by adolescents; 2) to search deeply the psychological well-being level of the studied group; 3) to resolve the strategies used by adolescents with hi psychological well-being level, and if this strategies are different of the ones used by adolescents with low psychological well-being level. Methodology: 1) Design: comparative – descriptive study; 2) Sample: incidental; 3) Subjects: 150 adolescents between 13 and 18 years old of San Miguel de Tucumán (Argentina) and low socioeconomic level; 4) Techniques: Adolescent Coping Strategies (ACS) and Adolescent Well Being Scale (BIEPS-J) under Casullo adaptation. Results: Significative differences were found between coping strategies of adolescents with hi and low psychological well-being level, so as between coping strategies and gender.